Samotność i doświadczenie mistyczne - Bizior-Dombrowska, Magdalena (Filozofia Chrześcijańska, 2015)
The article is an attempt of analysis of the category of loneliness in the mystical experience. The loneliness is a natural space of cognition and a necessary condition of the contemplation enabling the experience of God, but it is also irremovable element of all stages of the mystical experience. Three of the principle problems of this question were subjected to the analysis. Faithful loneliness constituting the essence of the concept of anachorese. From such point of view the isolation from the world (as well as the escape from the body) turns out to be a way to experience of God. Holy loneliness as a durable spiritual state connected with narrow path of the dark contemplation of St. John of the Cross (mystical loneliness in God and for God). Inner loneliness (Eckhart’s seclusion as a basis of the project of inner man).